PERKEMBANGAN FISIK ANAK AKHIR DAN PERKEMBANGAN PSIKOSOSIAL PADA MASA REMAJA - Annisa, Annisa (FAKULTAS ILMU TARBIYAH DAN KEGURUAN UNIVERSITAS SAINS AL-QUR'AN, 2023)
The aim of this research is to describe the physical development of late childhood and the psychosocial development of adolescents. Researchers then summarize and present data regarding physical and psychosocial development based on the results of literature studies. The results of analysis and previously published literature data show that everyone experiences childhood and adolescence, during which time individuals will experience many changes, including physical, cognitive, psychological development, and child adaptation is very necessary to support their development.